2010
DOI: 10.1111/j.1540-8175.2010.01206.x
|View full text |Cite
|
Sign up to set email alerts
|

Does a New Ultrasound Flow Modality Improve Visualization of Neonatal Pulmonary Veins?

Abstract: Blood flow imaging may improve the visualization of the pulmonary veins in neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…We have previously found that TTE with the new flow imaging technique BFI may improve the visualization of interatrial blood flow in children and the PV in neonates. 18,19 In this transesophageal echo study, we compared this technique with the current reference methods for ASD sizing BSD and PV imaging (pulmonary angiography). We have described and quantified the agreement between the corresponding BSD and BFI ASD measurements and assessed repeatability of BFI measurements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously found that TTE with the new flow imaging technique BFI may improve the visualization of interatrial blood flow in children and the PV in neonates. 18,19 In this transesophageal echo study, we compared this technique with the current reference methods for ASD sizing BSD and PV imaging (pulmonary angiography). We have described and quantified the agreement between the corresponding BSD and BFI ASD measurements and assessed repeatability of BFI measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In its current implementation, the method BFI is limited to imaging shallow depths (<10 cm), suitable for instance for vascular imaging and imaging in pediatric cardiology. 18,19,28 However, getting closer to the heart through the esophagus implies that the method should also have potential for cardiac imaging in adults using TEE. Our study had a variation in patient size from 6.2 to 67.5 kg which demonstrates this potential.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations